2019 25th Conference of Open Innovations Association (FRUCT) 2019
DOI: 10.23919/fruct48121.2019.8981519
|View full text |Cite
|
Sign up to set email alerts
|

Keyphrase Generation: A Multi-Aspect Survey

Abstract: Extractive keyphrase generation research has been around since the nineties, but the more advanced abstractive approach based on the encoder-decoder framework and sequenceto-sequence learning has been explored only recently. In fact, more than a dozen of abstractive methods have been proposed in the last three years, producing meaningful keyphrases and achieving state-of-the-art scores. In this survey, we examine various aspects of the extractive keyphrase generation methods and focus mostly on the more recent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 77 publications
2
8
0
1
Order By: Relevance
“…They have been following a decreasing trend, falling from 32 % to 11 %. A similar trend is reported in other recent surveys [2,7]. We also observed that for the human evaluation process, existing studies usually involve a few human experts or some dozens of students.…”
Section: Nlg Evaluation Trendssupporting
confidence: 89%
“…They have been following a decreasing trend, falling from 32 % to 11 %. A similar trend is reported in other recent surveys [2,7]. We also observed that for the human evaluation process, existing studies usually involve a few human experts or some dozens of students.…”
Section: Nlg Evaluation Trendssupporting
confidence: 89%
“…There was an opposite trend about the works that carry human evaluation only. They have been decreasing steadily, same as reported in [3] and [9]. We also noticed that most human evaluations involve a few domain experts or tens of university students.…”
Section: Text Quality Evaluationsupporting
confidence: 80%
“…Keywords are a subset of words or phrases from a document that can describe con-cepts or topics covered in the document [57], [58]. They are commonly used to annotate articles or other documents, and are essential for the categorization and fast retrieval of such items in digital libraries [59].…”
Section: B: Methods 2: Automatic Annotationmentioning
confidence: 99%